Evaluation of the Signing Information Mid-West Project - Conama, John (PAUL Partnership, Limerick, 2008)
This report centres on the review of the Irish Sign Language/English interpreting services provided in the Mid-West via the “Signing Information Mid-West” service. This was established under the aegis of Enhancing Disability Services (EDS). The EDS is administered by the Department of Justice, Equality and Law Reform, and is operated by the PAUL Partnership. The service had employed an Irish Sign Language/English interpreter to undertake assignments in the Mid-West. A part-time development worker was also appointed with the goal of increasing awareness of the Signing Information service. Part of the funding contract includes the requirement to conduct a review of service provision to date. On the completion of the review, a report was given to the committee responsible for implementing the service
Keywords: Deaf studies; Irish Sign Language; Signing; Ireland